Essential managerial attributes of the nowadays nursing service manager in the South African context - Jooste, K (Curationis (Pretoria), 2003)
Nursing service managers need certain essential managerial attributes in taking the lead in effective management of the nowadays health care organisations in South Africa. Major changes in restructuring and human resources planning are taking place through transformation of health services and specific managerial attributes are needed in this scenario. Without nursing service managers with the necessary managerial attributes, change in the health care environment will be hampered and planning, organising, directing and control of the delivering of quality care will be negatively influenced. The research problem was addressed in the following question that guided the study: Which essential attributes/characteristics should a nursing service manager possess to run a health care service effectively? It was unclear what the opinions of all level of nurse managers were regarding the necessary managerial attributes the health services manager currently need to run the current health care services effectively. This study aimed at highlighting the necessary attributes of the nowadays nursing service manager in running a health care institution in the current health care environment of South Africa. Purposive sampling was done and forty-five functional, middle and top-level managers registered for a second year degree course in Health Services Management at a South African university participated in the study. The findings indicated important managerial and leadership attributes, which the current nursing service manager should possess. This article will only discuss the important managerial attributes needed. A conceptual framework came to the fore according to which an example of a self-evaluation instrument was compiled for nursing service managers for future use. The results of the data analysis indicated that the nursing service manager should promote good interpersonal relationships with colleagues, subordinates and patients through the attributes of openness, being inviting and empowering behavior. The purpose of this article is to make nursing service managers more aware of the necessary attributes they should possess and should develop to manage nursing services more effectively.